Sikh identity : continuity and change - Singh, Pashaura; Barrier, N. Gerald (Norman Gerald); University of Michigan. Sikh Studies Program (New Delhi : Manohar, 1999)
Contributed papers presented at a seminar held on August 29-31, 1996.
Includes bibliographical references.
Keywords: Sikhs -- Ethnic identity -- Congresses; Sikhs -- History -- 20th century -- Congresses